Construir el vacío : Dos arquitecturas de NP2F - Lella, Leonardo
Sobre la obra de NP2F.
Keywords: NP2F ARCHITECTES; CHAS, FRANÇOIS; GUÉRIN, NICOLAS; LONG, FABRICE; MAITRE DEVALLON, PAUL; ESTUDIOS DE ARQUITECTURA; TEORIA; CRITICA; TRAYECTORIA PROFESIONAL